Body shape phenotype, TYG trajectory and the risk of digestive system cancers - Kai, Zixiang; Liu, Chenan; Zhang, Qingsong; Wu, Shouling; Yun, Keming (Frontiers in Nutrition, 2025)
BackgroundThe triglyceride-glucose (TyG) index and unhealthy body shape have been shown to indicate the level of insulin resistance in the body and are associated with various chronic diseases. However, the longitudinal pattern of change in relation to the risk of digestive system cancers remains unclear.MethodsAll participants were drawn from a large prospective cohort study, the Kailuan Study. Latent mixture modeling was used to identify similar shared TyG index trajectories among participants who underwent annual physical examinations between 2006 and 2010. Principal component analysis was used to evaluate the body shape characteristics of participants. Cox regression models were used to investigate the relationship between the TyG index trajectories and the risk of digestive system cancers.ResultsA total of 53,350 participants were included in the study, with an average age of 49.5 (11.7) years. Five distinct TyG index trajectories were identified. During a median follow-up of 11.0 years, 804 participants developed digestive system cancer. Four characteristic phenotypes of body type were identified. Compared with a single measurement of the TyG index, TyG index trajectories better predicted the risk of digestive system cancer. After adjusting for potential confounders, the hazard ratios for developing digestive system cancers in the moderate low-stable, moderate high-stable, high-stable, and high-increasing groups compared with those of the low-stable group were 1.16, 1.42, 1.45, and 2.48, respectively. Consistently, as the trajectory changes, the components loads of body shape also constantly changes. Similar trends were observed for the risk of colorectal and gastric cancer.ConclusionThe TyG index trajectory is better than a single TyG index measurement for predicting the risk of digestive system cancers. Long-term maintenance of a high TyG index trajectory is associated with a less healthy body shape phenotype and an increased risk of digestive system cancers, especially colorectal cancer and gastric cancer.